Forest Structure of 26-Year-Old Planted Mangroves - Ruhuddien Pandu Yudha (Journal of Sylva Indonesiana, 2021)
The mangrove ecosystem in Bintuni Bay, West Papua, Indonesia has been sustainably managed for more than three decades for timber utilization. Since there are only few mangrove areas that utilized for logging in Indonesia, data on growth and forest structure of post-harvest mangrove forest could become valuable information as a reference for sustainable management on the ecosystem. This study conducted in a permanent plot (1.6 ha) which established and planted in 1994 using 5 dominant and commercial species in Bintuni Bay. Rhizophora apiculata has the best growth compared to other species, while Ceriops tagal experienced the poorest growth. From all trees individual, 24.27% were categorized as multi stem trees with maximum of 8 stems that could be occurred from one single tree and contributed to increase total volume of the stands up to 33%. Bruguiera gymnorhiza has the highest percentage of multi stem trees covering 65.87% of total trees individual. In general, forest structure was not significantly different in various spacing distance. Merchantable volume for 5 planted species at 26-year-old stand was estimated to be 310.99 m3 ha-1 with extractable biomass of 247.08 ton ha-1. Planted mangroves can provide sufficient standing stock for future utilization in managed mangrove forests.